(untitled) (Acta Entomológica Chilena, 2022)
A new species of the genus Teutoperla, T. maulina n. sp. (Plecoptera: Gripopterygidae: Gripopteryginae) is described. Descriptions of male, female, nymph and egg are given. Fenology and morphological variation of adults are provided. The known geographical distribution of the new species is limited to the Cordillera de la Costa of the VII Región of Chile.